Étendue et limites de l’obligation de reclassement à l’égard des personnes présentant une inaptitude en France - Sophie Fantoni-Quinton (Perspectives Interdisciplinaires sur le Travail et la Santé)
The obligation to reclassify medically disabled workers is a legal obligation in France. It is however not unlimited. Numerous lawsuits exist regarding the increased importance given by judges for to this obligation whose framework deserves to be better defined, clarified, and established. Otherwise, the initial aim, namely to avoid the unemployment of disabled workers, may not be achieved. First, the actual jurisprudence built on the legal principles of the French labour code must be surveyed, particularly regarding the starting point, the central role played by the occupational health physician, the boundaries of this obligation, as well as the burden of proof and the penalties in case of noncompliance. These need to be considered in order to better understand where the current reclassification requirements would gain more objectivity and more pragmatism.